Ética ou segurança? as questões da internet no currículo - Lamana, Rosa Maria Rodrigues (2014)
Understanding that public schools in the state of São Paulo to have internet access to students, this study aims to understand the perception of teachers on the need for work on Internet safety with the students and the state education system provides teachers some guidance in this theme for conducting orientation since the activities at schools using ICT integrated into learning situations. To develop the work we opted for the case study, involving 15 teachers and three school administrators of an integral program of the Institute, which in turn, has training for teachers hone the use of ICT in the teaching context. As an instrument for data collection was used questionnaires and semistructured interviews as well as documentary research. It was considered as a theoretical framework, authors such as Fernando José de Almeida, Manuel Castells, Zygmunt Bauman, Léa Fagundes da Cruz, Paulo Freire, Gimeno Sacristan, Patricia Peck Pinheiro, Cristina Moraes Sleiman, among others. Thus this thesis focuses on the importance of work ethics and safety on the internet within the school context across disciplines since the curriculum is a cultural construct and that internet access is part of mainstream culture, but believes that society as a whole, also has the responsibility of working on this theme with children and youth